2009
DOI: 10.1111/j.1439-0272.1992.tb02618.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spermatozoa of the rat in hyperprolactinaemia induced by Metoclopramide

Abstract: Metoclopramide (MCP) in doses of 2.2 mg kg-body weight, being administered intraperitoneally to rats for 14 d, provokes a premature release of germ cells in the testes. The number of spermatozoa is reduced. I n addition the spermatozoa exhibit defects of head and tail structures. After the administration of M C P for 14 d, followed by a 14-d break in applying the drug, the number of spermatozoa in the lumen of the epididymal duct continues to be low. Many spermatozoa are damaged. Only after a 66-dbreak in MCP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In the experimental study Amiri et al [37] used even doubled dose of MCP than we were for 21 days and found 2,5 fold increase of PRL concentration comparing to control rats. The capability of MCP to induce hyperprolactinemia was reported by others too [38,40].…”
Section: Discussionmentioning
confidence: 62%
“…In the experimental study Amiri et al [37] used even doubled dose of MCP than we were for 21 days and found 2,5 fold increase of PRL concentration comparing to control rats. The capability of MCP to induce hyperprolactinemia was reported by others too [38,40].…”
Section: Discussionmentioning
confidence: 62%
“…Because of this, both 52 mothers and physicians have sought drugs to address this concern [1]. 53 The available galactagogues are dopaminergic antagonists, which in- 54 crease serum PRL by counteracting the inhibitory influence of dopamine 55 (DA) on PRL secretion [3]. 56 Sulpiride (SUL) is mainly marketed as an antipsychotic drug and is 57 reported to selectively antagonize central dopaminergic receptors (D2, 58 D3 and D4) [4].…”
mentioning
confidence: 99%
“…Clinically, excessive secretion of PRL may interfere with the cyclic release of gonadotropin and may inhibit the peripheral activity of gonadotropin on the gonads (8). In the rat, its high concentration provokes a premature release of germ cells in the testes, the number of spermatozoa decreases and the sperm cells have morphological abnormalities in the head and tail (11). In men, low sperm counts have been correlated with hyperprolactinemia (12) and in women hyperprolactinemia is frequently diagnosed in patients with infertility and men-strual cycle irregularities (13).…”
mentioning
confidence: 99%